Effect of atmospheric-pressure air/He plasma on the surface properties related to ink-jet printing polyester fabric. (March 2017) - Zhang, Chunming; Zhao, Meihua; Wang, Libing; Yu, Miao
Abstract: Pigment inkjet printing shows more environmental advantages and can potentially enable cost-effective short-run for production. However, patterns directly printed with pigment inks have poor color yields and easily bleed. In the present study, polyester fabrics were surface modified with atmospheric-pressure air/He plasma. The effect of plasma treatment on various fabric properties such as the surface morphology, chemical compositions, surface energy and dynamic contact angles was investigated. Color strength and edge definition were used to evaluate the ink-jet printing performance of samples. The changing of the surface fixation of pigments on polyester fibers was also analyzed by scanning electron microscopy (SEM). Atomic force microscope(AFM) and X-ray photoelectron spectroscopy (XPS) analyses indicated the increase in surface roughness and the oxygen-containing polar groups reinforced the fixation of pigments on the fiber surface. This work explores a novel approach for the atmospheric-pressure plasma, which can provide its important application in enhancing the surface properties and ink-jet printing performance of fabrics. Highlights: Effect of atmospheric-pressure air/he plasma on the surface properties of ink-jet printing fabric was studied. Air/He plasma gave hydrophilicity on polyester surface and decreased contact angle to 18°. The roughness of polyester increased and pit-like structures appeared on the surface after plasma treatment. XPS confirmed the generation of new functional groups on polyester fabric. Relationship between wettability, fixation of pigments, anti-bleeding performance and color strength.